The Impact of Workplace Inclusion and Work-Life Balance on Workplace Happiness (Study at the Tanjungkarang Regional Office IV of PT Kereta Api Indonesia (Persero)) - Tribuana Ningrum; Ribhan (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
The paradigm of human resource management (HR) has been significantly changed by the introduction of artificial intelligence (AI) after 2024. The HR function no longer focuses on administrative work, but becomes a strategic partner that uses technology to help make decisions, talent management, and improve employee experience. This study aims to analyze the transformation of HR strategies after 2024, identifying the key competencies that HR needs. The research method uses a Systematic Literature Review (SLR) of ten scientific articles published between 2024 and 2026. These articles were obtained via academic databases like Scopus, Google Scholar, ScienceDirect, and Emerald Insight. The results show that AI improves efficiency and analytical capabilities in HR functions, but its success depends on digital skills, ethical technology, and employee mental readiness. To ensure equitable and humane AI adoption, employees must learn a hybrid of skills, such as data analytics, interpersonal skills, ethical leadership, and change management skills.